2009
DOI: 10.1590/s0102-46982009000100014
|View full text |Cite
|
Sign up to set email alerts
|

O que não tem remédio, remediado está?

Abstract: RESUMO: Temos observado um aumento significativo na prescrição de medicamentos psiquiátricos para toda sorte de sofrimentos cotidianos. Sabemos que as crianças não têm sido poupadas dessa lógica de tratamentos. A escola, por sua vez, tem apelado intensamente ao saber médico para "corrigir" os problemas apresentados por seus alunos. A prática descrita brevemente está sustentada por uma biologização cada vez mais bem-sucedida de nossa condição humana, ou seja, parece que chegou o tempo de o homem viver de perto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 1 publication
0
3
0
12
Order By: Relevance
“…Similarly Guarido and Voltolini (2009) in a psychoanalytic and grounded in Foucault debate, argue that there is a disclaimer from teacher to consider that absence of learning is due to physical problems, leaving "few gaps for that education to be seen as a link between adults and children that can result in some kind of transformation" (p. 255).…”
Section: The School Behind the Records-description Of Students: An Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly Guarido and Voltolini (2009) in a psychoanalytic and grounded in Foucault debate, argue that there is a disclaimer from teacher to consider that absence of learning is due to physical problems, leaving "few gaps for that education to be seen as a link between adults and children that can result in some kind of transformation" (p. 255).…”
Section: The School Behind the Records-description Of Students: An Inmentioning
confidence: 99%
“…The authors say that Brazil is the second largest consumer of Ritalin, a drug indicated for the treatment of ADHD, which was renamed as the "obedience drug" as it provides opportunities for educators to solve the difficulties presented in school, that is for the behaviors considered to be inappropriate to the school environment. Guarido and Voltolini (2009), expressing concern and rejection to this model that aims to pathologizing human experiences in order to control what comes out of the norm, so sadness turns into deppression, anguish and anxiety disorder, problems with writing in dyslexia, agitated behavior in ADHD, and (unfortunately) among other examples.…”
Section: Prescription Drugs: a Solution To Unexpected Behavior In Thementioning
confidence: 99%
“…Foi nesse contexto que se construiu a noção de infância como tempo do desenvolvimento e preparo para a vida adulta e momento de prevenção das doenças debilitadoras da saúde, das doenças mentais e da delinquência (Guarido & Voltolini, 2009).…”
Section: A Família Medicalizadaunclassified
“…Essa relação possibilitou a criação de classes especiais, bem como o surgimento de instituições especializadas e serviços de saúde vinculados à área da educação (voltados principalmente para a realização de diagnósticos de deficiências, problemas de aprendizagem e de comportamento), colocando em prática as teorias construídas a partir do entrecruzamento dessas disciplinas. A divisão normal/anormal tornou-se, portanto, a principal referência nas classifica-ções que receberam as crianças, sendo a principal justificativa para a criação de terapêuticas e mecanismos especiais de escolarização (Guarido & Voltolini, 2009).…”
Section: Psiquiatrização Da Infância E O Nascimento Da Criança Anormalunclassified
See 1 more Smart Citation